Neurotrauma and critical care of the spine - Jallo, Jack; Vaccaro, Alexander R. (Thieme, 2018)
""This book is the most useful summary of present knowledge about epidemiology, pathophysiology, assessment and management of spinal cord injuries today. It is a great book that deserves a widespread distribution among spine surgeons and physicians involved in the treatment of spinal injuries.""--European Journal of Orthopaedic Surgery & Traumatology Neurotrauma and Critical Care of the Spine, 2nd edition, by a distinguished critical care neurosurgeon, Jack Jallo, and a renowned spine surgeon, Alexander Vaccaro, incorporates salient components of the highly praised first edition. The updated